Involving Street Youth in Peer Harm Reduction Education: The Challenges of Evaluation - Poland, Blake D. (Can J Public Health, 2002)
Objectives: To describe and discuss the challenges in evaluation of a participatory action research with street-involved youth. Methods: A combination of quantitative and qualitative methods were utilized for both process and outcome evaluations. Process evaluation methods included in-depth individual interviews, focus groups, participant observation, and session debriefing forms. Summative evaluation research included focus testing of the harm reduction video and a survey of video users. Findings: Members of the youth team reported favourably on the experience, citing friendship, skills development, fun, and pride of accomplishment among the key benefits of participation. Political tensions arose because of the focus on reducing harm from drug use rather than encouraging abstension. The heavy demands of participatory research and development, resource constraints and the priority given to product development in these kinds of projects necessarily precludes extensive youth participation in the design, implementation and analysis of additional evaluation research. Even when resources are directed towards evaluation, there is a tendency to focus on data collection, which may limit time and resources for data analysis. Finally, there is an inclination to focus on the product development rather than dissemination and impact of the product. Interpretation: Despite the challenges inherent in participatory action research and its evaluation, this project was regarded as an empowering experience by the street youth who participated in it. It is worthwhile to direct resources to evaluation which optimally gives proportional attention to data collection as well as data analysis, and focusses not only on product development but also on its dissemination and impact.